2017
DOI: 10.2174/1574888x11666161028143224
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential, Challenges and Future Perspective of Cancer Stem Cells in Translational Oncology: A Critical Review

Abstract: Stem cell research is a rapidly developing field that offers effective treatment for a variety of malignant and non-malignant diseases. Stem cell is a regenerative medicine associated with the replacement, repair, and restoration of injured tissue. Stem cell research is a promising field having maximum therapeutic potential. Cancer stem cells (CSCs) are the cells within the tumor that posses capacity of selfrenewal and have a root cause for the failure of traditional therapies leading to re-occurrence of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Therefore, investigating the features and underlying mechanisms of cancer stem cells hold great promise for cancer diagnosis and therapy [20]. Stem cells in head and neck cancer, especially laryngeal cancer, have been isolated and characterized [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigating the features and underlying mechanisms of cancer stem cells hold great promise for cancer diagnosis and therapy [20]. Stem cells in head and neck cancer, especially laryngeal cancer, have been isolated and characterized [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Cancers result from continued proliferation and fail to differentiate and die in the proliferative zone; therefore, stem cells before grafts must be differentiated to help living body and prevent tumor formation [2,36,37]. Signals that control normal cell development may eventually lead us to insights in treating cancer by inducing tissue differentiation in a procedure called differentiation therapy [37,38]. Retinoid Acid (RA) is one of the chemicals which has been used in this approach [8], so was used as a chemical inducer in this study because of its ability to prevent cancer via differentiation enhancement has highlighted its role in the both research and clinical appliances [39].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that several mechanisms of salinomycin action are currently discussed. 5,[17][18][19] Studies by Zhang et al in in vivo and in vitro conditions demonstrated that salinomycin induces apoptosis in the cells of ovarian cancer resistant to cisplatin, apoptosis linked to the pathway of mitogen-activated protein kinase (MAPK). 20 Studies by Kaplan and Teksen on the stable ovarian cancer cell line (OVCAR-3) demonstrated the activity of salinomycin: 40% of cells underwent apoptosis within 24 h of exposure.…”
Section: Salinomycinmentioning
confidence: 99%
“…Most probably, this specific cell subpopulation is also linked to the initiation of the tumor (cancer initiating cells -CICs). 1,[3][4][5][6] Cancer stem cells manifest the capacity of self-renewal, DNA repair, persisting in the G1 or G0 cell cycle phases as inactive dormant cells and asymmetric cell division. They do not undergo apoptosis and they manifest overexpression of ABC genes, which is linked to their resistance to cytostatic drugs.…”
mentioning
confidence: 99%